Efficacy of Galidesivir against Ebola Virus Disease in Rhesus Monkeys. (4th October 2017) - Warren, Travis; MacLennan, Steve; Mathis, Amanda; Giuliano, Enzo; Taylor, Ray; Sheridan, William
Abstract: Background: The recent re-emergence of Ebola virus in the Democratic Republic of the Congo serves as a stark reminder of the 2013–2016 Ebola virus (EBOV), which resulted in >11, 000 deaths. To date, there are no approved therapeutics or vaccines for EBOV disease (EVD). Galidesivir (BCX4430) is an adenosine nucleoside analogue designed to inhibit viral RNA polymerase activity indirectly through non-obligate RNA chain termination. Galidesivir exhibits in vitro antiviral activity against a broad spectrum of negative- and positive-sense RNA viruses. In vivo, galidesivir has shown antiviral activity against various viruses and provides 100% protection against Marburg virus disease in cynomolgus macaques, when administered either 1 or 2 days post infection. Initial exploratory studies in a rhesus macaque model of EVD showed that 25 mg/kg galidesivir administered twice daily (BID) IM beginning immediately following viral challenge protected 100% (6 of 6) of animals. Methods: Pharmacokinetic modeling based on galidesivir levels in healthy and EBOV-infected animals predicted that a loading-dose regimen could decrease time to steady-state, potentially advantageous when extending the time of treatment initiation. To test the efficacy of a loading dose regimen, 100 mg/kg was administered BID either 2 or 3 days after challenge, followed by maintenance doses of 25 mg/kg BID for a total duration of 11 days. Results: Six of 6 (100%) rhesus monkeys survived after receiving loading doses on day 2, and 4 of 6 (67%) animals survived after receiving loading doses beginning day 3. In the dosing regimen that conferred 100% protection, the animals exhibited either no behavioral depression or only mild and transient behavioral depression. In all treated groups, there was a significant reduction of plasma viral RNA concentrations during the acute phase of disease. Conclusion: Galidesivir protects rhesus monkeys against an otherwise lethal EBOV challenge. Administered by IM injection, Phase 1 human clinical studies of single and multiple ascending doses have shown galidesivir to be generally safe and well tolerated up to 10 mg/kg daily for seven days. Additional clinical studies are planned to evaluate the safety and tolerability of galidesivir administered by IV infusion. Supported by NIAID (NIH), HHSN272201300017C. Disclosures: S. MacLennan, BioCryst: Employee, Salary. A. Mathis, BioCryst Pharmaceuticals: Employee, Salary. E. Giuliano, BioCryst: Employee, Salary. R. Taylor, BioCryst Pharmaceuticals: Employee, Salary. W. Sheridan, BioCryst Pharmaceuticals: Employee, Salary.